IMPLEMENTATION OF PBL MODEL TO TRAIN PROBLEM-SOLVING SKILLS OF KUALA LUMPUR INDONESIAN SCHOOLS’ STUDENTS - Kusaeni, Tsabita Na'ilatun Nahda; Inayah, Nailil; Siraj, Taufiq; Astutik, Julia (Science Education, Institut Agama Islam Negeri Ponorogo, 2024)
This research aims to determine students' problem-solving skills using the problem-based learning model assisted by Wordwall. This research was a quasi-experimental research posttest-only design. Samples were taken using saturated sampling techniques. The data collection method used a problem-solving skills test (posttest) and student response questionnaires. The results of the hypothesis test obtained a significance of 0.766 > 0.05, which means H0 was accepted. Based on the research results, it can be concluded that there is a difference in the problem-solving skills of students using the problem-based learning model compared to the conventional model using discovery learning, as seen from the average problem-solving aspects, although the differences are not significant. The students' response toward PBL assisted by Wordwall was positive. This research can be useful for developing a body of knowledge and a basis for other researchers' research, especially regarding the use of problem-based learning models assisted by wordwall game media to improve students' problem-solving abilities. Apart from that, research also provides new experiences for students in solving problem-based questions.